Creating customer value and the use of the product life cycle to generate strategic options for maturing low-cost service-retail markets -A case study on The Spirit Group value pub food retail concept"Two for One" - Twaites, Claire (2007)
This is a case study on a low-cost service retail concept known as "Two for One" a pub-food chain owned by The Spirit Group. The thesis aims to explore the nature and characteristics of the product life cycle for low-cost service retailers with the objective to establish strategic options. The nature of low-cost propositions is that price is the main strategic driver to compete for growth and market share. However in maturing markets where competition is high and margins are low, retailers seek alternative sources of differentiation. This study is important for two reasons: firstly, the literature on the product life cycle spans over 50 years, yet it does not study service retail markets-focusing instead on manufacturing or fast moving consumer goods. Secondly, not only is service retail a key area of modern business studies, but that there is a growing emergence of the low-cost provider in sectors such as short-haul flights (Easyjet); Multiple Grocers (Tesco); on-line retailers (Amazon) and pub-companies (J D Wetherspoons and TWO FOR ONE).